Stability of peptide nucleic acid influenced by peptoid-like sidechains : MD simulation study. - Yeo, Sven Hwea Jie. (2010)
Peptide nucleic acid (PNA) is one of the most promising candidates for next-generation antisense technology. Other than high specificity and ability to be engineered to target, it offers enhanced stability, fidelity and strand invasion capabilities. Rapid developments in this field include synthesis methods, cleavage studies and drug delivery systems. In this report, MD simulations of decamer heteroduplexes involving modified PNA were performed under periodic boundary conditions. Modifications are based on a recent work of Prof Liu’s lab, involving γ-N modification of PNA aeg backbone with amino-peptoid sidechain (APS) experimentally shown to retain its hybridisation affinity with DNA/RNA. Focusing on RNA, we analysed structural features as well as solute-solvent interactions to better understand the mechanisms governing hybridisation characteristics. We report that APS has a minor influence on the structure of the decamers which is quite localised. Solvent accessible surface of the modified base-pair experienced spikes in values during the 40ns simulations and solvation shells of the base-pair situated close to APS were disrupted up to 33%. It is probable that stability conferred could be attributed to desolvation and related effects, but further investigations need to be done. We put forward several candidates for cleavage moieties relevant to our intended application.